Informator . no. 89, 1981 - Biuro Informacyjne Regionu Środkowo-Wschodniego NSZZ "Solidarność", [duty ed. M. Sobieraj, W. Jackson] (NSZZ "Solidarność" Region Środkowo-Wschodni, 1981)
Creation and circulation: For trade-union use; After introduction of the Martial Law publication suspended. Republished underground in January 1982